Analysis Of Content Marketing Implementation On Kedai Twenties’ Social Media - Rudy Vernando Silalahi; Angel Maria Mawikere (FORBISWIRA FORUM BISNIS DAN KEWIRAUSAHAAN, 2023)
Kedai Twenties is a cafe that just opened in June 2021 and the problem faced by this cafe is the lack ofawareness and knowledge of Kedai Twenties as a cafe that is suitable for work or study. This research uses observationand interviews, as well as surveys conducted by distributing questionnaires to the target market from KedaiTwenties, as well as documentation from Kedai Twenties and research data from research institutions. The results ofthis research show that the content provided is in the form of a video that is appealing, engaging, and informative. Nanoinfluencers are also used in this video content to help boost brand awareness and knowledge of this cafe. The developedcontent is posted on social media platforms such as Instagram and TikTok. Instagram has reached 2,908 account,while TikTok has only 146. Meanwhile, the engagements for Instagram were 3,667, 101, 0, and 22, respectively, forplays, likes, and comments, as well as shares. In terms of engagement, TikTok received 163, 9, 1, and 2 plays, likes, andcomments, as well as 2 shares, respectively.